2007
DOI: 10.1063/1.2748043
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of attractive and repulsive ramp fluids: Integral equation and computer simulation studies

Abstract: Using computer simulations and a thermodynamically self-consistent integral equation we investigate the phase behavior and thermodynamic anomalies of a fluid composed of spherical particles interacting via a two-scale ramp potential (a hard core plus a repulsive and an attractive ramp) and the corresponding purely repulsive model. Both simulation and integral equation results predict a liquid-liquid demixing when attractive forces are present, in addition to a gas-liquid transition. Furthermore, a fluid-solid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 73 publications
(136 reference statements)
2
54
0
Order By: Relevance
“…This kind of procedures has already been successfully applied to the study of the fluid phase behavior of simple fluids [31][32][33][34] and fluid mixtures. 34 A number of advantages make this class of approaches a preferred tool for these problems.…”
Section: A Wang-landau Type Algorithmmentioning
confidence: 99%
“…This kind of procedures has already been successfully applied to the study of the fluid phase behavior of simple fluids [31][32][33][34] and fluid mixtures. 34 A number of advantages make this class of approaches a preferred tool for these problems.…”
Section: A Wang-landau Type Algorithmmentioning
confidence: 99%
“…They possess a repulsive core that exhibits a region of softening where the slope changes dramatically. This region can be a shoulder or a ramp [74][75][76][77] . Despite their simplicity, such models had successfully reproduced the thermodynamic, dynamic, and structural anomalous behavior present in bulk liquid water.…”
Section: Introductionmentioning
confidence: 99%
“…Models from both groups have presented us with many fruitful results regarding the anomalous behavior of liquids. Although the shapes of the potential tails of both groups are very different, they exhibit water-like anomalous behaviors (see e.g., [22][23][24][25][26][27][28][29][30][31][32] and references quoted therein). It has recently been shown that even weakly softened potentials are able to yield water-like anomalies, i.e., in this case anomalies arise without ever invoking (as usually done) the interplay between two repulsive length scales [33,34].…”
Section: Introductionmentioning
confidence: 99%